Protective Effect of Quercetin on Renal Tubular Cells and the Involvement with the Renin-Angiotensin-Aldosterone Axis - Canuto,Jader Almeida (2021)
Abstract Ischemia-reperfusion (I/R) plays an important role in the process of acute kidney injury (AKI) due to the generation of reactive oxygen species (ROS). Substances of natural origin have been studied in the prevention of oxidative damage related to I/R. Quercetin is a flavonoid with antioxidant potential and modulate enzymes, such the inhibition of the Rennin-Angiotensin System (RAS). The aim of this study is to evaluate the nephroprotective effect of quercetin against the I/R and analyze the inhibition of RAS. Rhesus monkey Kidney Epithelial Cells (LLC-MK2 line) were submitted to an in vitro ischemia/reperfusion model. After the reperfusion cells were treated with quercetin, the cell viability was accessed by the MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide) assay. Tubular cell damage was assessed by the Kidney Injury Molecule-1 (KIM-1) measurement. Oxidative stress was evaluated through Thiobarbituric Acid Reactive Substances (TBARS) and reduced glutathione (GSH). The evaluation of cell death and the mitochondrial depolarization were analyzed by flow cytometry. Quercetin prevents cell death reducing oxidative stress and preventing mitochondrial membrane depolarization. Molecular docking showed that quercetin prevents cell damage better than losartan and lisinopril, inhibitors of RAS. Quercetin has a potential to interact with type 1 angiotensin II receptor (AT1) with greater affinity through the formation of five hydrogen bonds of strong intensity.